(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In Uzbekistan, there are more than 10 places of pilgrimage that are sacred and revered by Christians and Muslims. Until modern times, on the territory of Uzbekistan there are revered by both Christians and Muslims “springs of Job”, the most famous of which is located in Bukhara.